Can Pentraxin-3 be a Candidate Marker in the Follow-Up of the Patients With Behçet’s Disease? - Banu ALPASLAN MESCİ and Banu İŞBİLEN BAŞOK and Hatice GÜL SAĞUN and Gökhan GÖNENLİ and; ddes KAVALA and; KASAPOĞLU GÜNAL and; EKİZ and Ferruh İŞMAN and Aytekin OĞUZ (Archives of Rheumatology, 2017)
Objectives: This study aims to assess the level of pentraxin-3 (PTX-3) as an inflammatory marker and compare it with C-reactive protein (CRP) levels in patients with Behçet’s disease (BD). Patients and methods: Forty-two patients with BD (15 males, 27 females; mean age 39.7±8.6 years; range 20 to 64 years) and 42 age- and sex- matched healthy controls (14 males, 28 females; mean age 40.8±8.2 year; range 25 to 60 years) were included in the study. Serum CRP and plasma PTX-3 levels were measured. Subgroup analyses were performed according to clinical manifestations of patients with BD. Results: Both PTX-3 and CRP levels were significantly higher in patients with BD than controls (1.33±0.29 vs 0.85±0.12, p<0.05 for PTX-3 and 0.71±0.13 vs 0.27±0.03, p<0.001 for CRP, respectively). Area under the curve was 0.633±0.062 vs 0.729±0.05, respectively. Mean PTX-3 and CRP levels were 1.1 vs 1.5, p=0.5; 0.5 vs 0.9, p=0.5; respectively, in patients with mucocutaneous involvement alone and with other involvements, whereas they were 0.9 vs 1.6, p=0.1; 0.5 vs 0.8, p=0.3; respectively, in patients with and without peripheral arthritis, and were 1.7 vs 0.9, p=0.06; 1.0 vs 0.5, p=0.07; respectively, in patients with and without uveitis. Conclusion: Although PTX-3 levels were higher in patients with BD than healthy controls, sensitivity and specificity of PTX-3 was not different than CRP in patients with BD.